2016
DOI: 10.1038/srep19623
|View full text |Cite
|
Sign up to set email alerts
|

Autologous leukocyte-reduced platelet-rich plasma therapy for Achilles tendinopathy induced by collagenase in a rabbit model

Abstract: Leukocyte-reduced platelet-rich plasma (LR-PRP) is a therapy for tendinopathy of the Achilles tendon (TAT); however, there is scarce information regarding LR-PRP effects in rabbit models of TAT. We compared, at 4 and 12 weeks (w), the LR-PRP and placebo (PBS) effects on ultrasonography, histology and relative gene expression of collagen types I (COL1A1) and III (COL3A1) and vascular endothelial growth factor (VEGF) in 24 rabbits with TAT induced by collagenase. The rabbits (treated with both treatments) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Animal models have been used extensively to study the onset of tendinopathy through overuse exercise of the tendon itself, 6 induced inflammation of the tendon and joint via injection of cytokines and drugs, 7,8 and unloading of rotator cuff muscles via botox injection, immobilization or nerve transection. 9-14 Animal models provide several advantages over other models, primarily the ability to manipulate mechanical forces externally without disrupting native tendon architecture or the junctions with muscle and bone, which are known to be critically important to tendon function.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models have been used extensively to study the onset of tendinopathy through overuse exercise of the tendon itself, 6 induced inflammation of the tendon and joint via injection of cytokines and drugs, 7,8 and unloading of rotator cuff muscles via botox injection, immobilization or nerve transection. 9-14 Animal models provide several advantages over other models, primarily the ability to manipulate mechanical forces externally without disrupting native tendon architecture or the junctions with muscle and bone, which are known to be critically important to tendon function.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that the presence of leukocytes in PRP preparations may be detrimental to healing, due to their involvement in the inflammatory response [ 27 ] causing loss of pain relief efficacy [ 28 ]. We avoided this complication, because our PRP was prepared with nearly complete absence of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies indicated that PRP could increase the expression of collagen types I and III and vascular endothelial growth factor and improve the healing and remodeling process of the tendon [76, 77]. A lot of studies demonstrating improved tendon healing using PRP compared with controls, but controversial clinical results exist when using PRP to treat Achilles tendinopathy [7884].…”
Section: Treatmentmentioning
confidence: 99%